Benzo(a)pyrene promotes migration, invasion and metastasis of lung adenocarcinoma cells by upregulating TGIF. (15th September 2018) - Yang, Haiyan; Zhang, Hongsheng; Pan, Teng; Wang, Haiyu; Wang, Yadong
Highlights: BaP treatment increased the expression of TGIF mRNA and protein. BaP treatment increased TGIF promoter-driven reporter gene expression. BaP treatment promoted H157 cell migration, invasion and metastasis. Silencing TGIF blocked BaP-induced H157 cell migration, invasion and metastasis. TGIF overexpression was related to lung adenocarcinoma metastasis and smoke status. Abstract: This study aimed to investigate the potential roles of TG-interacting factor (TGIF) in benzo(a)pyrene (BaP)-induced migration, invasion, and metastasis of lung adenocarcinoma cells. Cells were treated with different concentrations of BaP. MTT assays were used to measure cell proliferation. Quantitative real-time polymerase chain reaction (qRT-PCR) and immunoblots were applied to measure the TGIF expression. A dual-luciferase reporter gene assay was performed to assess the effects of BaP on TGIF promoter-driven reporter gene expression. Wound-healing, transwell, and tail vein metastasis assays were performed to evaluate migratory, invasive, and metastatic capacity. Our results showed that BaP treatment increased the expression of TGIF mRNA and protein. Additionally, BaP treatment enhanced TGIF promoter-driven reporter gene expression. We observed that BaP treatment promoted the migration, invasion, and metastasis of H157 cells, which could be blocked by silencing TGIF. The expression of TGIF mRNA was significantly higher in metastatic lung adenocarcinoma samples than in non-metastatic lung adenocarcinoma samples, and higher levels of TGIF mRNA expression were observed in metastatic lung adenocarcinoma samples from patients with a smoking history than in those from patients with a non-smoking history. Our findings suggest that BaP treatment promotes the migration, invasion, and metastasis of human lung adenocarcinoma cells by upregulating TGIF.